1970
DOI: 10.3329/jbau.v8i1.6392
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salinity on seed quality of wheat

Abstract: Effect of salinity on sprouting water uptake, ion uptake and metabolic efficiency of wheat seeds in the variety kanchan were studied in Jaydebpur. The treatments were 0, 4, 8, 12 and 16dS-m salinity level. The experiment was set in CRD with four replications. There were 50 seeds per petridish. Seeds were moistened with saline solution. Germination was recorded up to 72 hours with an interval of 12 hours. Water absorption rate was recorded up to 42 hours with an interval of 6 hours. Accumulation of Na+ and CI- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…Salinity interferes with the process of water absorption by the seeds. This subsequently inhibits the hydrolysis of seed reserves which ultimately delays and decreases seed germination (Begum et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Salinity interferes with the process of water absorption by the seeds. This subsequently inhibits the hydrolysis of seed reserves which ultimately delays and decreases seed germination (Begum et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the rate of coleoptile's emergence under high NaCl concentration was observed in other plants (Bounaqba, 1993) reflecting the slowdown in reserve mobilization to seedling (Prisco et al, 1981). Results indicated that salinity induced delay and decrease the germination percentage through lower water uptake and higher accumulation of Na + and Cl - (Begum et al, 2010). As salinity enhances osmotic pressure leading to a reduction in water absorbance, division and cell differentiation, which negatively affects metabolic and physiological processes.…”
Section: Kineticmentioning
confidence: 98%
“…According to Begum et al (2010), germination of seed depends on the utilization of reserved food materials of the seed. Salinity interferes with the process of water absorption by the seeds.…”
Section: Resultsmentioning
confidence: 99%